Study on domestic waste water treated using modified rice husk sequences slow sand filter (MRHSSSF) - Chee Wei, Wong (2013)
Malaysia is facing river pollution which mainly cause by domestic wastewater. On the other hand, rice husk as the by-product from rice mill created disposal and air pollution problem. Rice husk are believed can remove the water pollutants. The aim of this study is to design a compacted slow sand filter which called Modified Rice Husk Sequence Slow Sand Filter (MRHSSSF) as well as to determine the effectiveness of MRHSSSF in wastewater treatment. The optimum retention time of the system also was determined in this study. MRHSSSF is a system that comprised of 3 aerators, sand and rice husk integrated filter bed (0.15-0.3nmi sand size - 0.075-0.15mm activated rice husk size- 0.6-1 .1 8mm sand size ) where rice husk was soaked in 0.5 mole acid sulphuric for 20 minutes. In this study, MRHSSSF was used to treat the domestic wastewater in 8 days duration. Based on the result and analysis, the highest percentages of removal achieved by MRHSSSF in this study for turbidity, TSS, BOD, COD, E.coli, oil and grease, Iron (Fe), Lead (Pb), Zinc (Zn), TDS, Total coliform, are 98.08%, 100%, 100%, 96.12%, 100%, 97.59%, 100%, 100%, 61.19%, 50.17% and 22.79% respectively. The optimum retention time for the system is 3 hours since most parameters show good mean result. In the conclusion, MRHSSSF is a very cost effective compacted wastewater treatment system.